PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM STUDI PADA NEGARA ASEAN-5 - Yunita Lestari; Nurna Aziza; Nikmah; Andi Agus (UNIB Press, 2024)
The objective of this research is to analyze the impact of financial performance on stock prices in the ASEAN-5 countries. The financial ratios analyzed include, Liquidity Ratio, proxied by the Current Asset Ratio (CR), Profitability Ratios, proxied by Return on Assets (ROA) and Return on Equity (ROE), Solvency Ratio, proxied by the Debt to Equity Ratio (DER), Activity Ratio, proxied by the Total Asset Turnover (TATO). The data used in this research include financial data from companies listed on the stock exchanges of the ASEAN-5 countries during the period from 2020 to 2022. This study uses secondary data obtained from the websites of each country's stock exchange. The sample consists of 225 companies with a total of 675 data points. The data analysis method employed is panel data regression (Eviews 12). The results of the study indicate that the liquidity ratio (CR), solvency ratio (DER), and activity ratio (TATO) do not affect stock prices. This suggests that investors in the ASEAN-5 region do not primarily consider these three ratios in their investment decisions. Conversely, profitability ratios (ROA and ROE) are proven to affect stock prices. High profitability ratios increase investor confidence and interest, thereby driving up the company's stock price. These findings provide insights for company managers and investors in understanding the factors that influence stock prices in the ASEAN-5 capital markets.